2022
DOI: 10.1101/2022.07.31.22278258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of SARS-CoV-2 BA.4/BA.5 Omicron lineages with immune escape and clinical outcome

Abstract: Expansion of the SARS-CoV-2 BA.4/BA.5 Omicron lineages in populations with prevalent immunity from prior infection and vaccination has raised concerns about the association of these lineages with immune escape. Here we show that COVID-19 vaccination and documented prior infection are associated with reduced protection against infection with BA.4/BA.5. Compared to time-matched BA.2 cases, BA.4/BA.5 cases had 9% (95% confidence interval: 2-17%) and 27% (15-41%) higher adjusted odds of having received 3 and 4 COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Immunological observations from South Africa point to considerable immune escape of Omicron BA.4 and BA.5 from Omicron BA.1 elicited immunity, but much less so in those with vaccination (15). In other settings such as the United States, a higher risk of breakthrough infection with Omicron BA.4 or BA.5 was observed among previously vaccinated or infected individuals, indicating greater immune escape, but these breakthrough infections were associated with low severity (17). Cell-mediated immunity likely contributed to the lower levels of hospitalisation and mortality in the Omicron BA.4/BA.5 wave (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunological observations from South Africa point to considerable immune escape of Omicron BA.4 and BA.5 from Omicron BA.1 elicited immunity, but much less so in those with vaccination (15). In other settings such as the United States, a higher risk of breakthrough infection with Omicron BA.4 or BA.5 was observed among previously vaccinated or infected individuals, indicating greater immune escape, but these breakthrough infections were associated with low severity (17). Cell-mediated immunity likely contributed to the lower levels of hospitalisation and mortality in the Omicron BA.4/BA.5 wave (22).…”
Section: Discussionmentioning
confidence: 99%
“…Omicron sub-variants are more transmissible than previous VOCs, with greater immune escape, with BA.4/BA.5 showing reduced neutralization from antibodies induced by BA.1 infection, more so in the unvaccinated (14,15). Early data showed that Omicron BA.4/BA.5 waves had reduced severity in South Africa (16) and the United States (17).…”
Section: Introductionmentioning
confidence: 99%
“…First, whereas the EPIC-HR trial was conducted during the Delta (B.1.617.2) wave, our study confirms high effectiveness of nirmatrelvir-ritonavir in a period when most treated cases were likely infected with BA.4/BA.5 Omicron lineages. 15 Second, the EPIC-HR trial included only individuals who had no history of confirmed SARS-CoV-2 infection and who had never received a COVID-19 vaccine. Our study, however, showed a significant further benefit of treatment for preventing hospitalization in a cohort where 94% of recipients had received ≥1 COVID-19 vaccine dose, and 77% had received ≥3 doses.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis codes used to define ARI-associated hospital admissions are listed in Table S1. (15,20) 42 (41, 43) 53.9 (-8.4, 81.0) Treatment effectiveness is measured as (1 − adjusted hazard ratio) × 100%, comparing outcomes among individuals who received treatment to those who did not. Time at risk is measured from treatment dispense date, for treatment recipients, and from an equivalent number of days following testing for non-recipients.…”
Section: Data Sharing Statementmentioning
confidence: 99%
See 1 more Smart Citation